(untitled) (Conferencea, 2024)
This thesis outlines the causes of corruption in the tax system, the challenges of its elimination, and objective solutions to the issue. It highlights key measures such as digitization, increasing accountability, ensuring independent oversight, and adopting best practices from countries with low corruption levels to reduce corruption in the tax system effectively.